2021
DOI: 10.1093/ofid/ofab079
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Activation Is Correlated With Monocyte Activation in HCV/HIV Coinfection and Declines During HCV Direct-Acting Antiviral Therapy

Abstract: Background Immune activation markers associate with morbidity and mortality in HIV and HCV infection. We investigated how T-cell and monocyte activation are related over the course of HCV direct-acting antiviral (DAA) therapy during HCV/HIV coinfection. Methods PBMC from AIDS Clinical Trials Group (ACTG) A5329 participants and a single-site separate cohort, treated with DAAs, were analyzed for central memory (CM)/effector mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…On the other hand, analysis of CD8+ T cells showed important changes such as an increased CD28, CD45RO, and HLA-DR expression without a concomitant decrease in CD38 for long-term follow-up outcome. These data are in contrast with those previously reported by other authors showing a reduction in immune activation induced by treatment [15,38]. The difference could be due to the sample size or the characteristic of the study population (e.g., fibrosis stage, cirrhosis, different anti-HCV treatment, DAA duration for SVR).…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, analysis of CD8+ T cells showed important changes such as an increased CD28, CD45RO, and HLA-DR expression without a concomitant decrease in CD38 for long-term follow-up outcome. These data are in contrast with those previously reported by other authors showing a reduction in immune activation induced by treatment [15,38]. The difference could be due to the sample size or the characteristic of the study population (e.g., fibrosis stage, cirrhosis, different anti-HCV treatment, DAA duration for SVR).…”
Section: Discussioncontrasting
confidence: 99%
“…Chronic HCV infection is associated with elevated plasma levels of systemic markers of immune activation such as sCD14, sCD163, IL-18, Mac-2BP, ATX, and IP-10, more so in patients with advanced liver disease [ 19 22 ]. The levels of some markers normalize following DAA therapy initiation (such as IP-10) while other markers often remain elevated (such as sCD14) [ 19 , 23 , 24 ]. Residual immune activation following DAA therapy has been attributed to presence of liver fibrosis and cirrhosis prior to DAA treatment [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a recent report evaluating T-cell and monocyte activation over the course of HCV direct-acting antiviral (DAA) therapy in HCV/HIV coinfection [ 39 ] showed that after therapy CD4 T-cell activation positively correlated with monocyte activation. This phenomenon did not exist before DAAs therapy and was possibly related to restored liver function or residual immune activation.…”
Section: Discussionmentioning
confidence: 99%